FORMAL AND INFORMAL TEACHING APPROACHES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Teachers of new languages may employ either formal or informal teaching approaches. The formal method of teaching grammar focuses on the structure of the language's grammar (Harmer, 2015). Students learn about various grammatical structures as well as how to construct meaningful sentences in this form of instruction. The teaching technique is predicated on the notion that grammatical requirements play a significant role in the formation of accurate sentences. The informal style, on the other hand, emphasizes on the pupils' capacity to communicate smoothly in the new language. As a result, the instructor tells the pupils about the influence of many aspects in language use, such as tone differences, using this technique. The traditional way of teaching new languages is ineffective.